ZIF-assisted construction of magnetic multiple core-shell Fe3O4@ZnO@N-doped carbon composites for effective photocatalysis. (14th December 2019) - Huang, Shoushuang; Zhao, Junru; Wu, Chenghao; Wang, Xin; Fei, Siming; Zhang, Qian; Wang, Qing; Chen, Zhiwen; Uvdal, Kajsa; Hu, Zhangjun
Graphical abstract: Magnetic multiple core-shell Fe3 O4 @ZnO@N-C composites are successfully fabricated. As synthesized composites exhibit efficient photocatalytic performance and magnetic recovery and possess high stability and recyclability. Highlights: Magnetic-Fe3 O4 @ZnO@N-C composites are successfully synthesized. This Fe3 O4 @ZnO@N-C composite has multiple core-shell structures. Fe3 O4 @ZnO@N-C composites show efficient photocatalytic performance. Fe3 O4 @ZnO@ N-C composites possess very good stability and recycling. Abstract: Magnetic Fe3 O4 @ZnO@nitrogen-doped carbon (Fe3 O4 @ZnO@N-C) composites with multiple core-shell structures have been successfully synthesized by calcination of ZIF-8 coated Fe3 O4 @ZnO core-shell nanocrystals. The morphologies and microstructural characteristics are investigated by X-ray diffraction, Fourier-transform infrared spectrometer, transmission electron microscopy, X-ray photoelectron spectroscopy, physical adsorption of nitrogen, and UV–vis diffuse reflectance spectroscopy. The photocatalytic performances are tested by degrading methylene blue (MB) in aqueous solutions under the irradiation of imitative sunlight. The photocatalytic trials indicate that the Fe3 O4 @ZnO@N-C composites exhibit improved degradation efficiency compared to the Fe3 O4 @ZnO precursor. The photocatalytic efficiencies of the as-prepared Fe3 O4 @ZnO@N-C composites towards MB are 93% under irradiation of imitative sunlight for 90 min and still maintained to be 87% after 6 recycles, which shows very good stability and recyclability. Nitrogen-doped carbon is believed to extend the absorption spectra to the visible-light region. The photodegradation kinetics via using the as-prepared Fe3 O4 @ZnO@N-C composite as a novel photocatalyst are systematically investigated.